Forests as Topographic Mappers in the Redwoods - Lyman, C. K. (Indian Forester, 1946)
One of the war jobs taken over by the Fores Service was the topographic mapping of the coastal area of northern California. The rigid technical requirements, the giant redwoods and tho foggy weather combined to make an unusually tough assignment. How the major difficulties Were overcome makes an interesting addition to the annals of tho forestry profession.